SITUATION-BASED LEARNING UNTUK MENINGKATAN KEMAMPUAN CREATIVE PROBLEM SOLVING MATEMATIS SISWA SD - Tiurlina, Tiurlina; Isrok’atun, Isrok’atun (Mimbar Sekolah Dasar, 2014)
In general, the learning activity that occurs is more emphasis on the process of learning to learn to answer questions rather than learn how to present the question. Students do not learn how to bring mathematical problems (problem posing) are of interest to them, from a mathematical situation faced. This results in the problem of finding the weak ability of students, so the ability of the idea of finding and problem solving students also weak. Idea finding, problem finding and problem solving is an aspect of the ability of Creative Problem Solving (CPS) mathematically. Therefore, the ability of CPS becomes very necessary to be developed in the learning of mathematics. For this purpose, the necessary mathematics learning more digging ability in presenting the problem and resolve the concerns raised by the students themselves, using the Situation-Based Learning (SBL). This study used a quasi-experimental. The results of the study concluded that an increase in the ability to obtain mathematical CPS students getting SBL better learning than students who received conventional learning significantly. CPS strongest mathematical ability of the students are in fact finding aspects, while CPS mathematical abilities of the students in the weakest aspect of finding acceptance. Keywords: mathematical situation, a mathematical problem, creative problem solving mathematical, situation-based learning.